Self-Efficacy of internship nursing students in dealing with Palliative patients - Rani Asyuni Sipayung; Tuti Pahria; Atlastieka Praptiwi (Journal of Nursing Care, 2019)
Palliative care is one of the practice areas that is perceived difficult by nurses and nursing students. Students tend to avoid seeing patients with the deteriorating condition. This research aimed to identify the self-efficacy of internship nursing students in facing palliative patients within communication, management of the patient, and multidisciplinary teamwork components. This study was a descriptive quantitative. Samples were recruited from a population of internship nursing students at Faculty of Nursing Universitas Padjadjaran using a total sampling technique (n=159). Data were collected using Self-Efficacy Palliative Care scale (SEPC). Data were analyzed using mean scores calculated from the total scores of each respondent. The results showed that more than half of the respondents had a low level of self-efficacy. In terms of its components, students’ self-efficacy in communication,  multidisciplinary team collaboration, and patient management had a mean score of 38.24 (SD 10.35), 39.21 (SD 9.44), and 48.18 (SD 9.56) respectively. Based on the results, it is recommended to develop an active learning strategy for internship nursing students, especially in the aspects of communication, patient management, and multidisciplinary team collaboration.